Los neuroderechos. Una nueva frontera para los derechos humanos - Orías, Ramiro (2022)
This paper discusses the current challenges posed by the recent developments and impacts of neurosciences and neurotechnologies for the protection of human rights, as well as the risks that in particular may affect the freedom, thought and physical integrity of the human person, expanding into a new frontier, an area previously little known to the legal world. To this end, this article first addresses the background and progress in the progressive development of an international regime on Human Rights and Neurosciences / Neurotechnologies, expressed in the adoption of various soft law instruments at the universal and regional levels. Then, it describes some elements of the regional discussion that has been advancing in the construction of inter-American principles on the subject, in the light of the rights established in the American Convention on Human Rights, and finally the text proposes some concluding thoughts, identifying the legal challenges to be addressed by the inter-American system.